2001
DOI: 10.1152/physrev.2001.81.3.1353
|View full text |Cite
|
Sign up to set email alerts
|

Spectrin and Ankyrin-Based Pathways: Metazoan Inventions for Integrating Cells Into Tissues

Abstract: The spectrin-based membrane skeleton of the humble mammalian erythrocyte has provided biologists with a set of interacting proteins with diverse roles in organization and survival of cells in metazoan organisms. This review deals with the molecular physiology of spectrin, ankyrin, which links spectrin to the anion exchanger, and two spectrin-associated proteins that promote spectrin interactions with actin: adducin and protein 4.1. The lack of essential functions for these proteins in generic cells grown in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
984
5
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 864 publications
(1,015 citation statements)
references
References 442 publications
(328 reference statements)
14
984
5
12
Order By: Relevance
“…The Fas2 tumor invasion and blocked BC migration phenotypes indicate that Fas2 is both necessary and sufficient to inhibit invasion, and that its pattern of expression predicts epithelial invasion. (Goodman et al, 1997); Dlg-4.1 (Lue et al, 1996); Nrg-Ank (Hortsch et al, 1998); 4.1-Spec/Act and Ank-Spec/Act (Bennett and Baines, 2001). Scrib, which is also localized to BLJ, is not shown since we found that its loss does not cause invasion as defined in this work.…”
Section: Spatio-temporal Expression Of Fas2 Predicts Epithelial Invassupporting
confidence: 42%
“…The Fas2 tumor invasion and blocked BC migration phenotypes indicate that Fas2 is both necessary and sufficient to inhibit invasion, and that its pattern of expression predicts epithelial invasion. (Goodman et al, 1997); Dlg-4.1 (Lue et al, 1996); Nrg-Ank (Hortsch et al, 1998); 4.1-Spec/Act and Ank-Spec/Act (Bennett and Baines, 2001). Scrib, which is also localized to BLJ, is not shown since we found that its loss does not cause invasion as defined in this work.…”
Section: Spatio-temporal Expression Of Fas2 Predicts Epithelial Invassupporting
confidence: 42%
“…Several means of silencing E-cadherin gene expression in gastric carcinoma have been observed, including methylation of the E-cadherin promoter, E-cadherin gene truncation mutations and loss of heterozygosity of the E-cadherin locus (Rosivatz et al, 2002;Brooks-Wilson et al, 2004;Scartozzi et al, 2004;Yang et al, 2004). However, these mechanisms account for only a portion of the E-cadherin-negative gastric carcinomas.…”
Section: Disruption Of E-cadherin Function By Tgf-b Adaptor Elfmentioning
confidence: 99%
“…Thus, in a mixture of aI, aII, bI, and bII, the concentration or the level of (aII/bI) 2 would decrease slightly in the presence of a specific bI-interactor (e.g., a cellular protein), as the interactor competes with aII for bI and may reduce the amount of (aII/bI) 2 formation. However, the concentration of (aII/bII) 2 should not change, as bI-interactor does not compete with aII for bII. Similarly, cellular proteins with structural features similar to scFv F11 may affect the tetramer concentration of (aII/bII) 2 , but not (aII/bI) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Spectrin and other proteins such as actin, ankyrin, and protein 4.1 form a cytoskeletal network. 2,3 The most common and well studied spectrin isoforms are erythroid aIand bI-spectrin, and nonerythroid aII-and bII-spectrin. 1 It is generally accepted that aI-, aII-, bI-, and bII-spectrin are all expressed within neurons, [4][5][6][7][8] with aI-and bI-spectrin found in neuronal cell bodies, dendrites, and postsynaptic terminals of neurons, 9 whereas aII-and bII-spectrin are found in the axon and presynaptic termini.…”
Section: Introductionmentioning
confidence: 99%